A rational approach towards novel modulators of necroptosis - Ferreira, Maria Beatriz Tomaz (2020)
Necroptosis is a regulated form of necrosis that occurs in response to a cellular damage or infection. It is independent of caspases, occurring under conditions in which the classical pathway of cell death by apoptosis is inhibited. The execution of this type of cell death involves the recruitment of kinases as the RIPK1 and the RIPK3, which give rise to a complex necrosome and lead to the recruitment of the MLKL and consequent phosphorylation, triggering a necroptosis process. RIPK1 and RIPK3 are involved in a wide variety of pathologies for which they currently lack effective treatments, such as stroke, myocardial infarction or acute pancreatitis. Nec-1 was the first known inhibitor for necroptosis, acting through the blockade of RIPK1 activity. However, this presents some problems such as non-specificity for the target. As such, new inhibitors of RIPK1 have been developed, seeking to present better pharmacokinetic and pharmacodynamic properties, focusing on their stability and activity in vivo. Due to the great relevance of these new targets in the treatment of pathologies in which necroptosis is involved and based on a preliminary study of 21 Oxazol-5-(4H)-one derivatives in BV2 and L292 microglial cell lines, a lead compound, OXA 12, was found has an inhibitory activity similar to Nec-1. From OXA 12 and using the Erlenmeyer-Plöch reaction new OXAs were synthesized with the introduction of several groups. Besides these OXAs were further synthesized, altering the hippuric acid by other groups such as the hydrazones. These new compounds were subsequently used for biological evaluation.